Chemical Composition and Cytotoxic Activity of Eucalyptus torquata Luehm. and Eucalyptus salmonophloia F. Muell. Trunk Bark Essential Oils against Human SW620 and MDA‐MB‐231 Cancer Cell Lines. Issue 11 (27th October 2021) - Lahmadi, Ghofrane; Lahmar, Aida; Znati, Mansour; Elaieb, Mohamed Tahar; Khouja, Mohamed Larbi; Ascrizzi, Roberta; Flamini, Guido; Harrath, Abdel Halim; Chekir‐Ghedira, Leila; Jannet, Hichem Ben
Abstract: In recent years, there has been a growing interest in the screening of natural active ingredients from Eucalyptus essential oils because of their evident importance in practical utility and their undeniable therapeutic properties. Based on this, the aim of the present study was to investigate the chemical profile of the essential oils of the trunk bark of Eucalyptus torquata Luehm. (ETEO), and E. salmonophloia F. Muell. (ESEO), growing in Tunisia. The in vitro cytotoxic properties of the extracted EOs were also evaluated against two human cancer cell lines: breast carcinoma cell lines MDA‐MB‐231 and colorectal cancer cell lines SW620. The analysis by gas chromatography coupled with mass spectrometry (GC/MS) led to the identification of 32 compounds from the ETEO, with the dominant constituents being the monoterpenes trans‐ myrtanol (73.4 %) and myrtenol (4.7 %), and the apocarotene ( E )‐ β ‐ionone (3.9 %). In the case of ESEO, 29 compounds were identified with trans‐ myrtanol (25.0 %), decanoic acid (22.1 %), nonanoic acid (9.8 %), γ‐elemene (6.5 %), γ‐maaliene (5.5 %), and α‐terpineol (5.3 %) as the main components. The cytotoxicity of EOs against the two chosen cell lines was tested using Crystal Violet Staining (CVS) assay and 5‐fluorouracil as a reference drug. The two EOs exhibited a significant dose‐dependent inhibition against the viability of the used cell lines. Their inhibitory effects were particularly observed towards SW620 colon carcinoma cells with IC50 values of 26.71±1.22 and 22.21±0.85 μg/mL, respectively, indicating that both oils were more cytotoxic for SW620 cells compared to MDA‐MB‐231 one. Abstract :